Mothers’ acceptance towards Breastfeeding Support Group Program in Badung District, Bali - Siwi, Luh Putu Anggyani Raka; Aryani, Putu; Utami, Ni Wayan Arya (Universitas Udayana, 2022)
Background and purpose: Coverage of exclusive breastfeeding in Badung District is lower than the Bali Provincial and national level. Breastfeeding Support Groups (BSG) have been proven effective to overcome breastfeeding barriers in several developing countries. This study aims to explore the acceptance of breastfeeding mothers toward the BSG Program in Badung District, Bali Province. Methods: A qualitative study with an exploratory approach was conducted in Kekeran and Punggul Villages, two villages where BSG was first implemented in Badung District. In-depth interviews were conducted with fifteen breastfeeding mothers as the key informants and supporting informants, including two village officials, two village midwives and two cadres. Interviews were recorded, transcribed, analysed thematically, and presented in a narrative form. Results: Breastfeeding mothers in Kekeran and Punggul Villages showed positive attitudes and thoughts by stating that BSG is essential. The acceptance was shown by their willingness to attend and participate fully and enthusiastically. Mother's good knowledge about BSG and the success of exclusive breastfeeding led to high motivation to participate in the program. Other supportive factors were positive experiences, mainly the direct practice of breastfeeding, and support from in-laws, husbands, midwives, and village officials, while the inhibitory factors were myths and social sanction. Conclusion: BSG was well accepted by mothers with good knowledge and perception, positive experiences, high motivation, and positive social supports as supporting factors. It is recommended to develop activities according to mothers' needs adopted to local culture and customs, as well as to involve multi-stakeholders.